The Necessary Accidental - Ashraf Jamal (The Thinker)
This essay on William Kentridge’s ideas and practice, in particular regarding his multi-media theatrical works, was prompted by a visit to Zeitz MOCAA to see his retrospective in 2019. Watching a documentary on the making of the ‘The Head and The Load’, I was struck by the production’s frenzied energy, and the exhaustive attempt to break down any predictive or conclusive vision. This has always been Kentridge’s approach – his animated works are exercises in a deconstructive erasure. I have addressed this matter elsewhere, in my essay ‘Faith in a Practical Epistemology: On Collective Creativity in Theatre’ (Predicaments of Culture in South Africa, 2005), but on this occasion, while watching the documentary, it was Nietzsche’s view in Contra Wagner which proved the trigger, namely, that ‘Wagner’s art is sick. The problems he brings to the stage – purely hysteric’s problems – the convulsiveness of his affects, his over-charged sensibility … the instability he disguises as a principle’. While Kentridge does not share Wagner’s reactionary ideology, I argue that there is a connection between the two whose root lies in a decadent sensibility. And the peculiarly late-modern Western crisis that underlies it.